PELATIHAN DAN PEMBUATAN POSTER MANAJEMEN WAKTU UNTUK SISWA - Adrian T Hasim; Nurlisa S Amantulu (Journal of Community Services on Multidisciplinary Sciences, 2026)
This project aims to increase students' awareness and skills in effective time management through educational training and poster-based media. This project is motivated by students' low awareness of efficient time management, which has an impact on discipline, late completion of assignments, and an imbalance between academic and non academic activities. The main objectives of this project are to help students understand the basic concepts of time management, improve their ability to create daily schedules, and encourage their creativity in conveying time management messages through communicative posters. The methods used include short training sessions on the basic principles of time management, followed by individual or group activities to create educational posters. The expected outcomes are an increase in students' awareness of the importance of time management, their ability to create daily schedules that reflect good time management skills, and the production of educational posters that can be part of the school's internal campaign. This project shows that early learning of time management skills has a positive impact on improving students' discipline, responsibility, and independence.